Ethnobotanical Knowledge and Market Value of Medicinal and Aromatic Plants in Joshimath Block of Chamoli Uttarakhand, India - Kaparawan, Praveen; Nautiyal , B. P.; Bisht, Anand (International Journal of Economic Plants, 2024)
The present study has been carried out during 2021 to 2022 in Joshimath block of district Chamoli, Uttarakhand, India to document the ethnomedicinal uses of medicinal and aromatic plants and their marketing patterns. Of 54 plant species, 47 herb, 4 shrubs, and 3 trees specieswere used for curing a total 21 diseases such as fever, rheumatism, jaundice, intestinal problems etc. Rhizome/tuber/roots (34.48%), followed by leaves (20.68%), fruits/seeds (17.24%), whole plant (6.89%), flower (5.17%), stem/bark (5.17%), root and leaf (5.17%), leaves and flower (1.72%), leaves and stem (1.72%), root and fruit (1.72%) were used for curing different ailments.A total 13 MAPs and 5 MAPs products were recorded in use and marketed during the survey.The maximum retail price (Rs 2000/Kg) was observed in Potentilla fulgens whereas, the minimum retail prize (Rs 125/Kg) was observed in Saussureacostus . Oil of Rosa damascena had maximum retail price (Rs 7000-8000/Litter) and the minimum retail price (Rs 210/L) was observed in Rose water . Among 54 medicinal plants, 6 species were critically endangered, 7 endangered, 6 near threatened, and 5 vulnerable species showed high demand in the market and greater potential towards curing of different ailments.